Skin Lesions Score in Large White Yorkshire Piglets during Postweaning Period Reared on Different Floor Types - Shende, G. P.; Prasad, R. M. V.; Chandra, Sarat; Prakash, Gnana; Nagalakshmi, D.; Srinivas, Reddy M. (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted during Jully, 2020 to November, 2020 at Pig Unit, Livestock Farm Complex (LFC), College of Veterinary Science, Rajendranagar, Hyderabad, Telangana, India to study the effect of different types of floors on performance, behavior, and carcass traits of Large White Yorkshire piglets during different phases of growth under intensive system. 24 Large White Yorkshire piglets were reared on four types of flooring systems consisting of 6 piglets in each group i.e., T1 (control group) reared on the concrete floor, T2 rubber mat, T3 elevated slatted floor, and T4 on soil floor from weaning to 126 days. The piglets were individually examined for the presence of skin lesions of the carpus, hock, abdomen, and teats, face, and tail every fortnight from the start of the experiment. The severity of the lesions was scored as 0, 1, 2, or 3. The initial mean skin lesion score of LWY piglets was 0.20±0.09, 0.30±0.10, 0.23±0.10, and 0.20±0.07 and it was decreased to 0.00±0.00, 0.00±0.00, 0.20±0.09, and 0.00±0.00 in T1, T2, T3, and T4 floor types respectively. Statistical analysis revealed non-significant (p>0.05) differences in mean skin lesion score among the piglets reared on four floor types during the initial, first, second, third, fourth, and fifth fortnight. The mean skin lesion score of piglets reared on the elevated slatted floor was higher during the sixth, seventh, eighth, and ninth fortnight and differed significantly with concrete, rubber mat, and soil floor.